Cultural politics in the Undhuh-Undhuh tradition within Javanese Christian Authority - Azharghany, Rojabi; Caecilia Arini Palupi; Dodik Harnadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Undhuh-undhuh is a traditional celebration of the East Javanese Christian Church (GKJW) that combines the values of Christian teachings found in the Bible with distinctive local Javanese culture and the agrarian traditions of Javanese society. This study aims to analyze and understand how the process of reproduction of cultural power occurs in the undhuh-undhuh celebration within the authority of GKJW Sambirejo, primarily using Chris Jenks’s perspective on cultural reproduction as its analytical framework. The study employs a qualitative approach using interpretative methods. Data collection techniques included observation, in-depth interviews and documentation. The findings indicate that undhuh-undhuh serves as a space for the transmission of cultural values and symbols across generations within the religious community. The older generation acts as the guardian of tradition, whilst the younger generation introduces innovations to ensure the tradition remains relevant in an increasingly modernised global world. This tradition preserves elements of local culture such as traditional dress, the use of the Javanese language in sermons and hymns, musical accompaniment featuring Javanese gending, and traditional food. This tradition strengthens social solidarity through collective activities such as mutual cooperation in event preparations and auctions. The acculturation of Christian values and Javanese culture is evident in the symbols of worship, which are adaptive yet retain their spiritual significance. This research emphasises the importance of intergenerational involvement in safeguarding the continuity of local traditions so that they remain relevant amidst social change.